STUDI ETNOGRAFI KOMUNIKASI PADA KETURUNAN CAMPURAN MELAYU - TIONGHOA DI KABUPATEN KARIMUN - ROSITA; SHOHILUL ABIDIN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The Malay and Chinese ethnic groups are the majority in the Karimun Regency. Tolerance between cultures is built by long term social interaction between these two different cultures. The marriage between the Malays and the Chinese inherit bilingual children. This study focuses on the use of dominant languages ​​in mixed Malay-Chinese descent that come from different languages, which is Malay and Teochew or Hokkien. This research is a qualitative descriptive study using studies of communication ethnography. Research data obtained from the process of observation and interviews. The results showed that the communication activities of mixed Malay Chinese descendants in Karimun took place according to their daily activities. Factors that affect a mixed Malay-Chinese can master both languages are in the teachings of parents. With the ability to speak in both languages, the variety of languages adapts to the topic, setting, and participants as well as the order of communication.